Environmental sustainability in urology Ökologische Nachhaltigkeit in der Urologie - Wullich, Bernd; Borchers, Holger; Eggersmann, Christian; Burger, Maximilian; Thöne, Marlene (Die Urologie, 2025)
Environmental sustainability has become increasingly important in recent years, not only in social discourse but also in the healthcare sector. The healthcare sector in Germany contributes significantly to total CO2 emissions, accounting for over 5%, and consumes roughly the same amount of resources. Areas that are particularly relevant to urology, such as pharmaceuticals, medical devices, and instrument logistics, are among the most intensive consumers of resources, alongside construction measures, the operation of clinics and practices, and food supply. In light of this, the German Society of Urology (DGU) has recognized the urgency of the situation and developed a sustainability strategy that includes all sectors of the field and aims to provide concrete perspectives for the responsible use of existing resources.
CRIS-Team Scopus Importer:2025-12-05
Keywords: Climate neutrality; Climate protection; Climate resilience; Environmental protection; Resource conservation